1987
DOI: 10.3133/cir968
|View full text |Cite
|
Sign up to set email alerts
|

Development of sinkholes resulting from man's activities in the Eastern United States

Abstract: Alternatives that allow avoiding or minimizing sinkhole hazards are most numerous when a problem or potential problem is recognized during site evaluation. The number of alternatives declines after the beginning of site development. Where sinkhole development is predictable, zoning of land use can minimize hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 3 publications
0
68
0
1
Order By: Relevance
“…This large, rapid decline in groundwater levels was the result of groundwater withdrawn for frost-freeze protection during January 2010 (Southwest Florida Water Management District, 2010). A large decline in groundwater levels near well fields and agricultural lands can remove the hydraulic support of overburden sediments lying above limestone cavities, resulting in sinkhole formation (Newton, 1986).…”
Section: S-44 Cypress and Starkey Central D S-68 Cypressmentioning
confidence: 99%
“…This large, rapid decline in groundwater levels was the result of groundwater withdrawn for frost-freeze protection during January 2010 (Southwest Florida Water Management District, 2010). A large decline in groundwater levels near well fields and agricultural lands can remove the hydraulic support of overburden sediments lying above limestone cavities, resulting in sinkhole formation (Newton, 1986).…”
Section: S-44 Cypress and Starkey Central D S-68 Cypressmentioning
confidence: 99%
“…With reference to the Eastern United States, Newton (1987) reports that since 1950 there have been more than 6500 sinkholes induced by man. More specifically, Williams and Vineyard (1976) carried out an inventory of sinkholes and subsidence events occurred in Missouri, and concluded that half of the cases were induced by human activities, with alteration of the natural drainage (52% of the cases) as main action, and highway construction (6,5%) and blasting (4,3%) as the less common.…”
Section: Interrelations With the Anthropogenic Environmentmentioning
confidence: 99%
“…Surface subsidence can develop within a matter of days when highly soluble rocks dissolve due to anthropogenic pressures (Martinez et al, 1998). The location of sinkhole collapse and speed of formation, rather than the diameter or depth, dictate the threat to human life and the potential for economic loss (Newton, 1987). To date, the Federal Emergency Management Agency reports that insurance claims relating to sinkholes, either natural or human-induced, in the United States totals $100 million annually.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, stress on and overuse of the Florida aquifer has led to several occurrences of emptied lakes, including Lake Jackson (1619 ha; 4,000 ac) and Lake Scott (115 ha; 285 ac) (Penson, 2002;McBride et al, 2011). Human-induced sinkholes often result from dewatering by wells, quarries, and mines in limestone environments (Newton, 1987;Fidelibus et al, 2011). The processes forming sinkholes can be enhanced by humaninduced change in the groundwater hydrologic regime by either inflows or outflows resulting from pumping activities (Benito et al, 1995;Martinez et al, 1998;Florea et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation